1990
DOI: 10.1039/c39900000964
|View full text |Cite
|
Sign up to set email alerts
|

Bioreduction with immobilized bakers' yeast in hexane using alcohols as an energy source

Abstract: Bioreduction with immobilized bakers' yeast proceeded smoothly in hexane by using alcohols, such as methanol, ethanol, and propan-2-01, instead of glucose, as an energy source; ethyl 3-oxobutanoate and ethyl benzoylformate were each reduced to the corresponding chiral hydroxy esters with a high enantiomeric purity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
0
12
1
2
Order By: Relevance
“…In this latter approach, as shown by Naoshima et al (19) for yeast, the organism is grown first under controlled conditions in an aqueous medium and then immobilized for later use as a biocatalyst in organic media. Even though the cells are not growing, they can remain viable during the course of reaction, thereby providing a means for regenerating depleted cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…In this latter approach, as shown by Naoshima et al (19) for yeast, the organism is grown first under controlled conditions in an aqueous medium and then immobilized for later use as a biocatalyst in organic media. Even though the cells are not growing, they can remain viable during the course of reaction, thereby providing a means for regenerating depleted cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, pode-se citar a síntese realizada por Mori e Takikawa 11 da (3S,11R)-3,11-dimetil-2-nonacosanona (3), feromônio produzido pelas fêmeas da barata, Blattella germanica (Orthoptera: Blattellidae), ou da (5Z,13S)-5-tetradecen-13-olida (4), sinergista do feromônio de agregação dos besouros do grão, Cryptolestes pusillus (Coleoptera: Cucujidae) (Figura 3) 12 .…”
Section: Figura 1 Enantiômeros Do Sulcatol (1)unclassified
“…Uma mistura de (5S,9S)-5,9-dimetil-heptadecano (10a), principal componente do feromônio sexual do bicho mineiro do café, Leucoptera scitella (Lepidoptera: Lyonetiidae), e seu isômero (5R,9S)-11a foram sintetizados tendo como precursor o (R)-citronelal (12). Este foi obtido através de resolução cinética do citronelal racêmico com fermento de pão, que reduziu seletivamente o enantiômero S-12 levando ao álcool 13.…”
Section: Alcanosunclassified
“…Previous studies have examined the use of immobilized whole cells for biocatalysis in organic solvents (22,23). It has been observed that cell selectivity can be manipulated through the use of specific inhibitors, cell immobilization, and the choice of organic solvent (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%